THE ROLE OF THE TEACHER IN FORMING THE SPIRITUALITY OF STUDENTS THROUGH MUSIC - M.SH. Djumaboyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the main tasks of forming the spirituality of students through national music and the role of the teacher.